Enzyme modified CNTs for biosensing application: Opportunities and challenges - Pundir M.; Prasher P.; Vasić K.; Leitgeb M.; Kumar A.; Prakash R.; Knez Ž.; Pandey J.K.; Kumar S. (My University, 2025)
Considerable biocompatibility, prospect of engineering the surface as per the deliberated application, and high accuracy of the results have driven the development of carbon nano tubes (CNTs) based biosensors. Enzyme catalyzed reactions occur under immensely milder physiological environments with high substrate specificity that minimizes the formation of side-products. Enzyme Immobilization represents the space-localization, or physical confinement of the enzymes that restrains their catalytic activity and improves their recyclability. The present article aims to provide a comprehensive record of the enzyme immobilization on the engineered CNTs, and their subsequent applications for the detection of various analytes. In addition, the recent advances in the functionalization techniques for enzyme-less detection of analytes on modified CNTs, their commercialization aspects and associated challenges is discussed. © 2021